We were the universe : a novel - Parsons, Kimberly King (Alfred A. Knopf, 2024)
"The trip was supposed to be fun. When Kit's best friend gets dumped by his boyfriend, he begs her to ditch her family responsibilities for an idyllic weekend in the Montana mountains. They'll soak in hot springs, then sneak a vape into a dive bar and drink too much, like old times. Instead, their getaway only reminds Kit of everything she's lost lately: her wildness, her independence, and--most heartbreaking of all--her sister, Julie, who died a few years ago. When she returns home to the Dallas suburbs, Kit tries to settle in to her routine--long afternoons spent caring for her irrepressible daughter, going on therapist-advised dates with her concerned husband, and reluctantly taking her mother's phone calls. But in the secret recesses of Kit's mind, she's reminiscing about the band she used to be in--and how they'd go out to the desert after shows and drop acid. She's imagining an impossible threesome with her kid's pretty gymnastics teacher and the cool playground mom. Keyed into everything that might distract from her surfacing pain, Kit spirals. As her already thin boundaries between reality and fantasy blur, she begins to wonder: Is Julie really gone?"--